Cats: the new challenge for rabies control in the state of Yucatan, Mexico - Salgado-Cardoso, Aurea Mariana; Olave-Leyva, José Ignacio; Morales, Ivonne; Aguilar-Setién, Alvaro; López-Martínez, Irma; Aréchiga-Ceballos, Nidia (Pathogens, 2024)
The growing population in Yucatan has led to the expansion of construction in the Mayan jungle for tourist spaces, residential areas, and agriculture. Recently, rabies cases in cats (Felis catus) have increased in the state. This study aimed to perform antigenic and genetic characterization of the rabies viruses in felines and to present the spatial distribution and environmental features of the areas where these cases were reported. The ArcGIS software and R were employed to generate maps depicting the geographic locations of rabies cases in cats. A total of nine feline rabies cases occurred during the period 2003-2022. Three antigenic variants were detected: dog-related RVV1 (n = 1); vampire bat variant RVV3 (n = 1); and the canine-originated atypical variant (n = 7). Cases reported in Merida (n = 4) and Muna (n = 4) were localized to urban areas, while Cuncunul (n = 1) was rural. This study highlights the concerning resurgence of rabies infections in cats, emphasizing the looming threat of its reintroduction in dogs should vaccination rates diminish. The genetic affinity between the atypical variant and the canine virus underscores the urgent need for vigilance in maintaining high vaccination coverage across all susceptible species.
Gesehen am 07.04.2025